Numerical study of the recirculation zone behind a building in the neutral and stable atmospheric boundary layer - Hai, Duong Ngoc; Duc, Nguyen The (Vietnam Journal of Mechanics, 2002)
The objective of the paper is to study numerically, using k - Ɛ model, the circulation zone behind a building under neutral and stable conditions. The influences of wind speed, vertical gradient of the temperature, surface roughness and building height on the length and structure of the recirculation zone are investigated. The research result showed that the recirculation area extends from immediately behind the building to a distance of about 2.5 times, in maximum, of the dimension of the building. The recirculation zone's 1length increases with the increase of wind speed, decreases with the increase of vertical gradient of the temperature, decreases with the increase of roughness and increases with the increase of building height. Some exceptions of two last tendencies may occur for the cases of high surface roughness or high building, when the flow shift from a simple one-vortex to a complex multiple-vortex structure.